The Effect of Counseling Using Video and Booklet Media on The Level of Knowledge on Stroke Prevention in Hypertension Patients - Suratun, Suratun; Krisanty, Paula; Lusiani, Dewi; Sahat, Camilia S (Poltekkes Kemenkes Jakarta III, 2024)
Stroke is a cerebrovascular disease and is a problem throughout the world. Stroke is the third cause that can result in death and is a cause of invalidity/disability. Strokes in hypertension sufferers can be prevented by providing education using various media, including video media and booklets. The aim of this research is to determine the effect of counseling using video and booklet media on the level of knowledge of stroke prevention in hypertension patients. The research method uses a quasi-experimental pre-posttest with control design. The sample used was 30 respondents suffering from hypertension. Method analysis uses univariate and bivariate with dependent t-test statistics, while multivariate analysis using logistic regression test. The results of data analysis of respondent characteristics found that the majority of respondents were aged 60-74 years, female, had elementary-middle school education, and did not work in counseling groups with videos or booklets. The results of bivariate data analysis showed that there were differences in age and education level between the counseling groups using videos and booklets, but there were no differences in gender and employment status. There was a significant difference in the level of knowledge of stroke prevention in the counseling group with videos before and after the intervention (p value = 0.000) with a difference in knowledge score = 2.49, while in the counseling group with booklets before and after the intervention (p value = 0.000) with a difference in knowledge score = 1.44. When compared, the increase in knowledge scores in the video counseling group was higher than in the booklet counseling group. Multivariate test results showed that age, gender and education of hypertension sufferers had an effect on knowledge of stroke prevention with a value of p = 0.028. The conclusion is that there is an influence of counseling using video media and booklets on increasing knowledge of stroke prevention in hypertension sufferers and there is an influence of age, gender and education on knowledge of stroke prevention in hypertension patients.